Genetic association and frequency distribution in segregating generations derived from pigeonpea crosses - Ajay, B.C.; Byregowda, M.; Veerakumar, G.N. (The Indian Journal of Genetics and Plant Breeding, 2016)
Correlation and presence of genetic interactions was studied using F2 and F3 generations in three pigeonpea crosses for yield and its component traits. Most of the characters studied were positively skewed and were being governed by several genes indicating quantitative inheritance. Variance, skewness and kurtosis have also indicated that homozygosity has increased over the generation in pigeonpea crosses. Cross BRG 1 x ICP 8863 was found better than other two crosses (TTB 7 x ICP 8863 and TTB 7 x ICPL 87119) in providing high yielding segregants displaying parental diversity. Seed yield and other associated characters such as plant height and number of pods per plant had complementary gene action with other genes governing these characters. Yield increase is possible by following rigid selection for yield and its component characters. A shift in correlation coefficients between the generations was recorded which is likely to be attributed to difference in gene complementation of linkage blocks and an indication of unstable nature of breeding population.